2023
DOI: 10.3390/antibiotics12101514
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Anti-Efflux Activities of Cinnamon Essential Oil against Pan and Extensive Drug-Resistant Pseudomonas aeruginosa Isolated from Human and Animal Sources

Mohamed A. I. Abdelatti,
Norhan K. Abd El-Aziz,
El-sayed Y. M. El-Naenaeey
et al.

Abstract: Pseudomonas aeruginosa is notorious for its ability to develop a high level of resistance to antimicrobial agents. Resistance-nodulation-division (RND) efflux pumps could mediate drug resistance in P. aeruginosa. The present study aimed to evaluate the antibacterial and anti-efflux activities of cinnamon essential oil either alone or combined with ciprofloxacin against drug resistant P. aeruginosa originated from human and animal sources. The results revealed that 73.91% of the examined samples were positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…The results agreed with the results of Miladi [ 48 ] who conducted a study to evaluate the anti-efflux activities of five EOs components (eugenol, carvacrol, thymol, p-cymene, and γ-terpinene) alone or in combination with tetracycline against S. aureus ATCC 25923. Our results are also in line with those of Abdelatt and his co-workes who showed that there was a significant decrease in the expression levels of MexA and MexB genes of P. aeruginosa isolates treated with cinnamon oil when compared to the non-treated ones [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results agreed with the results of Miladi [ 48 ] who conducted a study to evaluate the anti-efflux activities of five EOs components (eugenol, carvacrol, thymol, p-cymene, and γ-terpinene) alone or in combination with tetracycline against S. aureus ATCC 25923. Our results are also in line with those of Abdelatt and his co-workes who showed that there was a significant decrease in the expression levels of MexA and MexB genes of P. aeruginosa isolates treated with cinnamon oil when compared to the non-treated ones [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is acknowledged that the ability of either P. aeruginosa or S. aureus to be resistant is aggravated. These bacterial infections increase the morbidity and mortality rates in both humans and animals [49,50]. This growing concern has resulted in an insistent need for the development of alternative, simple, cost-effective, and ecologically friendly approaches to mitigate bacterial resistance [51].…”
Section: Discussionmentioning
confidence: 99%